Hindlimb Immobilization, But Not Castration, Induces Reduction of Undercarboxylated Osteocalcin Associated With Muscle Atrophy in Rats. (5th July 2016) - Lin, Xuzhu; Hanson, Erik; Betik, Andrew C; Brennan‐Speranza, Tara C; Hayes, Alan; Levinger, Itamar
ABSTRACT: Undercarboxylated osteocalcin (ucOC) has been implicated in skeletal muscle insulin sensitivity and function. However, whether muscle mass and strength loss in atrophic conditions is related to a reduction in ucOC is not clear. We hypothesized that both immobilization and testosterone depletion would lead to reductions in ucOC, associated with not only the degree of muscle atrophy but also changes to atrophy signaling pathway(s) in male rats. We subjected 8‐week‐old male Fischer (F344) rats to 7 days of hindlimb immobilization 10 days after castration surgery. Hindlimb immobilization, but not castration, resulted in a significant reduction in ucOC (30%) and lower ucOC was correlated with the degree of muscle loss and muscle weakness. ucOC levels, the expression of ucOC‐sensitive receptor G protein‐coupled receptor, class C, group 6, member A (GPRC6A), as well as the activity of extracellular signal‐regulated kinase (ERK) and 5′ adenosine monophosphate–activated protein kinase (AMPK) were associated with the expression and activity of a number of proteins in the mammalian target of rapamycin complex 1 (mTORC1) and Forkhead Box O (FOXO) signaling pathways in a muscle type–specific manner. These data suggest that ucOC may have other effects on skeletal muscle in addition to its insulin sensitizing effect. © 2016 American Society for Bone and Mineral Research.